EFEK MAGNUS PADA PERMAINAN TENIS MEJA - Agus Nuramal; Aprilman Deviya; Arie Vatresia (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2024)
The Magnus effect is about the formation of pressure difference around a cylindrical or spherical projectile rotating in the flow of fluid. This difference causes forces acting on the projectile changing the direction of the projectile movement. Little understanding to Magnus effect concept is necessary for every activist in the sport area playing with ball. Discussing about the Magnus effect for the direction case of the ball in table tennis made them interested, e.g. the cases of empty shots, top spin, back spin, and side spin each produces different ball direction characteristics.